Fluid-Structure Interaction Analysis of Parachute Finite Mass Inflation - Xinglong Gao; Qingbin Zhang; Qiangang Tang (International Journal of Aerospace Engineering)
Parachute inflation is coupled with sophisticated fluid-structure interaction (FSI) and flight mechanic behaviors in a finite mass situation. During opening, the canopy often experiences the largest deformation and loading. To predict the opening phase of a parachute, a computational FSI model for the inflation of a parachute, with slots on its canopy fabric, is developed using the arbitrary Lagrangian-Euler coupling penalty method. In a finite mass situation, the fluid around the parachute typically has an unsteady flow; therefore, a more complex opening phase and FSI dynamics of a parachute are investigated. Navier-Stokes (N-S) equations for uncompressible flow are solved using an explicit central difference method. The three-dimensional visualization of canopy deformation as well as the evolution of dropping velocity and overload is obtained and compared with the experimental results. This technique could be further applied in the airdrop test of a parachute for true prediction of the inflation characteristics.